Density-dependent effects on the reproductive outcome of a native tree at tropical restored habitats - Ballarin, Caio S.; Hachuy-Filho, Leandro; Fontúrbel, Francisco E.; Amorim, Felipe W. (Forest ecology and management, 2022)
•Density-dependent effects influence plant reproduction output in restoration sites.•Increasing tree density enhances fruit set, but also the abundance of pre-dispersal seed predators.•Seed germination rates represent the net effect of plant density on plant reproduction.•The influence of density-dependent effects must be accounted during restoration planning and management. Plants are involved in different interactions with animals that may have contrasting effects on their reproductive output. However, as multitrophic interactions are resource-mediated and density-dependent, the frequency at which these interactions occur is modulated by the demographical characteristics of the populations of interacting species. For example, while plant aggregation may increase pollinator attraction and consequently, pollination success, an increased seed set may also attract more seed predators. Therefore, the intensity of pollination and seed predation events may affect plant population dynamics. Although multitrophic plant-animal interactions are crucial for maintaining biodiversity in terrestrial ecosystems, they have seldom been studied together, especially in restored habitats. To fill this gap, we used five restoration sites that used Inga vera trees at different densities to evaluate how density-dependent effects impact fruit set, seed predation, seed germination rate and the number of viable germinated seeds (i.e., the net effect of pollination and seed predation). Using structural equation models to assess the isolated effects of each predictor variable in each response variable and the cascading effects of each response variable on another, we found that density-dependent effects influenced I. vera reproduction. While I. vera trees in high density presented higher fruit set and seed predation rates, trees in low-density plantations presented lower fruit set, but seed predators consumed fewer seeds. The contrasting results of final seed germination rates revealed that density-dependent effects are pivotal to plant establishment and population dynamics. We argue that the study of density-dependent multitrophic plant-animal interactions is essential to guarantee that the efforts done in restoration initiatives can turn into successful results in terms of restoring ecosystem structure and stability.